2021
DOI: 10.1016/j.xplc.2020.100092
|View full text |Cite
|
Sign up to set email alerts
|

The maternally expressed polycomb group gene OsEMF2a is essential for endosperm cellularization and imprinting in rice

Abstract: Cellularization is a key event in endosperm development. Polycomb group (PcG) genes, such as Fertilization-Independent Seed 2 ( FIS2 ), are vital for the syncytium-to-cellularization transition in Arabidopsis plants. In this study, we found that OsEMF2a , a rice homolog of the Arabidopsis PcG gene Embryonic Flower2 ( EMF2 ), plays a role similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 75 publications
7
37
0
Order By: Relevance
“…Heat stress accelerates the suppression of these genes at 2 DAF time points, which likely accelerates the endosperm cellularization. These results are consistent with endosperm development in rice Embryonic Flower2 (OsEMF2a) mutant, wherein increased expression of cell-cycle genes leads to overproliferation of coenocytic endosperm and delays the cellularization, and this process has been linked to over-production of cytokinin (Cheng et al, 2021;Tonosaki et al, 2020). These results along with previous reports suggest that cytokinin-modulated suppression of cell-cycle genes likely accelerates the endosperm cellularization under heat stress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Heat stress accelerates the suppression of these genes at 2 DAF time points, which likely accelerates the endosperm cellularization. These results are consistent with endosperm development in rice Embryonic Flower2 (OsEMF2a) mutant, wherein increased expression of cell-cycle genes leads to overproliferation of coenocytic endosperm and delays the cellularization, and this process has been linked to over-production of cytokinin (Cheng et al, 2021;Tonosaki et al, 2020). These results along with previous reports suggest that cytokinin-modulated suppression of cell-cycle genes likely accelerates the endosperm cellularization under heat stress.…”
Section: Discussionsupporting
confidence: 89%
“…Recent evidence suggests an increase in JA levels and JA response during light and heat acclimation (Balfag on et al, 2019). In Arabidopsis, enhanced heat resilience by JA treatment and hyperheat-sensitivity of JA mutants suggest that JA positively regulates heat tolerance (Clarke et al, 2009;Kazan, 2015). Consistent with these findings, we found that JA responds to heat stress in young seeds.…”
Section: Discussionsupporting
confidence: 89%
“…This scenario suggests gene duplication is a major evolutionary force shaping plant PRC2, most likely in a species-or genus-specific manner (Table 1). Nevertheless, the distinct PRC2 complexes and their functions in cereal growth and development remain to be elucidated [24,25,[40][41][42][43][44]. To maintain H3K27me3 homeostasis, it is reasonable to have opposite players to remove the mark on targets (eraser).…”
Section: Writers and Erasers Of H3k27me3 In Plantsmentioning
confidence: 99%
“…CLSM was performed as described previously (Cheng et al, 2020). Images of the PI-stained embryos were taken using an LSM710 (Zeiss) microscope with excitation/emission wavelengths of 559/619 nm.…”
Section: Sectioning Staining and Microscopic Observationmentioning
confidence: 99%
“…The maize used in this study was grown in the experimental field of Biogle GeneTech in Xishuangbanna, Yunnan Province, China. Because the seeds produced by osnf-yb7 were inviable, the mutants used were propagated asexually by ratooning as described previously (Cheng et al, 2020). The rice and maize seeds were germinated in a growth chamber.…”
Section: Plant Growth Conditionsmentioning
confidence: 99%